(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
This study assessed the impact of climate change induced disaster on crops and fisheries production at Bhola Sadar and Monpura upazila of Bhola district, Bangladesh during January to June 2018. The study was gathered primary data from primary observation (PO), questionnaire survey (QS), focus group discussion (FGD), and key informant interview (KII). Secondary data were collected from Upazila Agricultural Office and Upazila Fisheries Office of Bhola Sadar and Manpura upazila and moreover, climatic data were collected from Bangladesh Meteorological Department. Results of the study found that trend analysis indicates overall annual maximum temperature increased for Kharif-I, Kharif-II and Rabi season. Average annual minimum temperature also increased for Kharif-I season but decreased for Kharif-II and Rabi season. Study also found that for all cropping season average relative humidity was increased. Annual average rainfall exhibited decreasing trend for Kharif-I and Rabi season but increased for Kharif-II season in (1990-2019) time period. The Aus, T. Aman, Boro and Mung bean was dominant cropping pattern in Kharif-I, Kharif- II and Rabi season in Bhola district. Overall, Aus rice production in Kharif-I season increased but in 2009, 2013 production was decreased because of cyclone Aila (2009) and Cyclone Mahasen (2013). T. Aman production hampered due to Cyclone Sidr (2007) and flood (2014) in Kharif-II season. In Rabi season Boro rice production lessen because of low rainfall and salinity intrusion. Overall, Mung bean production increase but in 2008 and 2009 production become hampered due to late cultivation because of Cyclone Sidr (2007). Fish production rate increase in Bhola specially Hilsha fish because of non-climatic factor like raid in non-fishing time, banned current net but fish production in pond become diminished due to infrequent natural disaster. Practicing of salt and flood tolerant varieties, floating bed vegetable cultivation, and mixed cropping system (mainly for Rabi season), enhanced expedition activities against catching mother Ilish in prohibition period, dredging in the heart of the river which can eventually reduce vulnerabilities and increase crop and fish production in the Bhola region. Int. J. Agril. Res. Innov. Tech. 10(1): 40-55, June 2020